Akuntabilitas NGO dan Kontrol Publik - Dedy Hernawan (Centre for Public Policy and Management Studies, 2004)
In the essence of NGO as living organization in public domain which is born from the public, acted as public agent and perform the mission on behalf of public, actually the public have the right to demand its accountibility. The accountability of NGO should be horizontally and vertically spread out into interrelated stakeholder. The expected accountability should be supported by the responsibility of their actions in the midst of public. The accountability will be effective if supported by trust and political will from the whole of stakeholder, so the accountability will manifest as founded control interaction on the base of positif social value of public. Kata Kunci : akuntabilitas NGO, publik, trust, good governance